HISTORIC-PEDAGOGICAL ANALYSIS OF THE POSTGRADUATE DOCTORS’ EDUCATION IN UKRAINE - Lysenko, Alexandra (Continuing Professional Education: Theory and Practice, 2019)
This article highlights the historical aspect of the formation of the doctors’ professional training in Ukraine since the time of the medical faculty of the Kharkiv University foundation in 1806. It presents the sequence of doctors’ postgraduate training system development. The author describes the experience of the Kharkov Medical Society in a question of the repeated demonstration courses for doctors in bacteriology implementation. The paper makes an inventory of the Medical Faculty Dean of the University of Saint Vladimir (now – Bogomolets National Medical University) professor M.A. Tikhomirov initiative (1900) for the commission establishment (among the most experienced professors of the faculty) to study issues of relevance, timeliness, and the establishing of doctors’ recurring courses; describes the role of the medical faculty of the University of Saint Vladimir at the first doctors’ universities repetitive courses introduction in Ukraine (1906), gives their approximate content, and provides rules for their organization and conducting in a six month duration period. Also this paper describes the practice of specialized postgraduate medical institutions creation such as: Clinical Postgraduate Medical Institute in 1918 (now – Shupyk National Medical Academy of Postgraduate Education), Kharkiv Doctors’ Advanced Training Institute in 1923 (now – Kharkiv Medical Academy of Postgraduate Education), Institute for Doctors’ Advanced Training in Odessa in 1926 (now – Zaporizhzhia Medical Academy of Postgraduate Education).